Impact of gratitude on posttraumatic growth in patients with coronary stent implantation: the mediating role of resilience and perceived social support - Lei, Shanyan; Zhang, Yujie; Yang, Fang (Frontiers in Public Health, 2025)
IntroductionThis study focused on investigating the extent of posttraumatic growth (PTG) and explored how resilience and perceived social support (PSS) mediate the relationship between gratitude and PTG among patients with a history of coronary stent implantation.MethodsA total of 242 patients with coronary stent implantation completed the Posttraumatic Growth Inventory, the Gratitude Questionnaire-Six Item Form, the Resilience Scale, and the Perceived Social Support Scale. We used structural equation modeling to evaluate the mediating effects of resilience and PSS on gratitude and PTG.ResultsThe mean score for posttraumatic growth was 55.54 (standard deviation = 15.01). Gratitude had a direct positive effect on PTG in patients with coronary stents (β = 0.126) and an indirect positive effect through the mediating effects of resilience and PSS (β = 0.105 and 0.081, respectively). Furthermore, resilience and PSS acted through serial multiple mediation effects in the relationship between gratitude and PTG.DiscussionGratitude positively affected PTG directly and indirectly through the single-and chain-mediating effects of resilience and PSS in patients with coronary stent implantation. These findings offer compelling evidence of the key interrelating mechanisms among protective factors that contribute to PTG. Therefore, accounting for the predictive influence of gratitude, resilience, and PSS in PTG when developing relevant intervention strategies may help improve patients’ quality of life.